Intrinsic link between PGRN and Gba1 D409V mutation dosage in potentiating Gaucher disease - Lin, Yi; Zhao, Xiangli; Liou, Benjamin; Fannin, Venette; Zhang, Wujuan; Setchell, Kenneth D R; Wang, Xiaohong; Pan, Dao; Grabowski, Gregory A; Liu, Chuan-ju; Sun, Ying (Human molecular genetics, 2024)
Gaucher disease (GD) is caused by biallelic GBA1/Gba1 mutations that encode defective glucocerebrosidase (GCase). Progranulin (PGRN, encoded by GRN/Grn) is a modifier of GCase, but the interplay between PGRN and GCase, specifically GBA1/Gba1 mutations, contributing to GD severity is unclear. Mouse models were developed with various dosages of Gba1 D409V mutation against the PGRN deficiency (Grn−/−) [Grn−/−;Gba1D409V/WT (PG9Vwt), Grn−/−;Gba1D409V/D409V (PG9V), Grn−/−;Gba1D409V/Null (PG9VN)]. Disease progression in those mouse models was characterized by biochemical, pathological, transcriptomic, and neurobehavioral analyses. Compared to PG9Vwt, Grn−/−;Gba1WT/Null and Grn−/− mice that had a higher level of GCase activity and undetectable pathologies, homozygous or hemizygous D409V in PG9V or PG9VN, respectively, resulted in profound inflammation and neurodegeneration. PG9VN mice exhibited much earlier onset, shorter life span, tissue fibrosis, and more severe phenotypes than PG9V mice. Glycosphingolipid accumulation, inflammatory responses, lysosomal-autophagy dysfunction, microgliosis, retinal gliosis, as well as α-Synuclein increases were much more pronounced in PG9VN mice. Neurodegeneration in PG9VN was characterized by activated microglial phagocytosis of impaired neurons and programmed cell death due to necrosis and, possibly, pyroptosis. Brain transcriptomic analyses revealed the intrinsic relationship between D409V dosage, and the degree of altered gene expression related to lysosome dysfunction, microgliosis, and neurodegeneration in GD, suggesting the disease severity is dependent on a GCase activity threshold related to Gba1 D409V dosage and loss of PGRN. These findings contribute to a deeper understanding of GD pathogenesis by elucidating additional underlying mechanisms of interplay between PGRN and Gba1 mutation dosage in modulating GCase function and disease severity in GD and GBA1-associated neurodegenerative diseases.